Reversible Cross-Linked Mixed Micelles for pH Triggered Swelling and Redox Triggered Degradation for Enhanced and Controlled Drug Release - Di Xiong; Liyang Wen; Shiyuan Peng; Jianchang Xu; Lijuan Zhang (MDPI AG, 2020)
Good stability and controlled drug release are important properties of polymeric micelles for drug delivery. A good candidate for drug delivery must have outstanding stability in a normal physiological environment, followed with low drug leakage and side effects. Moreover, the chemotherapeutic drug in the micellar core should also be quickly and “on-demand” released in the intracellular microenvironment at the tumor site, which is in favor of overcoming multidrug resistance (MDR) effects of tumor cells. In this work, a mixed micelle was prepared by the simple mix of two amphiphilic copolymers, namely PCL-SS-P(PEGMA-co-MAEBA) and PCL-SS-PDMAEMA, in aqueous solution. In the mixed micelle’s core−shell structure, PCL blocks were used as the hydrophobic core, while the micellar hydrophilic shell consisted of two blocks, namely P(PEGMA-co-MAEBA) and PDMAEMA. In the micellar shell, PEGMA provided hydrophilicity and stability, while MAEBA introduced the aldehyde sites for reversible crosslinking. Meanwhile, the PDMAEMA blocks were also introduced in the micellar shell for pH-responding protonation and swelling of the micelle. The disulfide bonds between the hydrophobic core and hydrophilic shell had redox sensitive properties. Reversible cross-linked micelles (RCLMs) were obtained by crosslinking the micellar shell with an imine structure. RCLMs showed good stability and excellent ability against extensive dilution by aqueous solution. In addition, the stability in different conditions with various pH values and glutathione (GSH) concentrations was studied. Then, the anticancer drug doxorubicin (DOX) was selected as the model drug to evaluate drug entrapment and release capacity of mixed micelles. The in vitro release profiles indicated that this RCLM had controlled drug release. In the simulated normal physiological environment (pH 7.4), the drug release of the RCLMs was restrained obviously, and the cumulative drug release content was only 25.7 during 72 h. When it came to acidic conditions (pH 5.0), de-crosslinking of the micelles occurred, as well as protonation of PDMAEMA blocks and micellar swelling at the same time, which enhanced the drug release to a large extent (81.4%, 72 h). Moreover, the drug release content was promoted further in the presence of the reductant GSH. In the condition of pH 5.0 with 10 mM GSH, disulfide bonds broke-up between the micelle core and shell, followed by shedding of the shell from the inner core. Then, the micellar disassembly (degradation) happened based on the de-crosslinking and swelling, and the drug release was as high as 95.3%. The MTT assay indicated that the CLSMs showed low cytotoxicity and good biocompatibility against the HepG2 cells. In contrast, the DOX-loaded CLSMs could efficiently restrain the proliferation of tumor cells, and the cell viability after 48 h incubation was just 13.2%, which was close to that of free DOX. This reversible cross-linked mixed micelle with pH/redox responsive behaviors is a potential nanocarrier for chemotherapy.